Effect of training in minimalist footwear on oxygen consumption during walking and running - Bellar, D; Judge, LW (Biology of Sport, 2015)
The present study sought to examine the effect of 5 weeks of training with minimalist footwear on oxygen consumption during walking and running. Thirteen college-aged students (male n=7, female n=6, age: 21.7±1.4 years , height: 168.9±8.8 cm, weight: 70.4±15.8 kg, VO2max: 46.6±6.6 ml · kg -1 · min -1 ) participated in the present investigation. The participants did not have experience with minimalist footwear. Participants underwent metabolic testing during walking (5.6 km · hr -1 ), light running (7.2 km · hr -1 ), and moderate running (9.6 km · hr -1 ). The participants completed this assessment barefoot, in running shoes, and in minimalist footwear in a randomized order. The participants underwent 5 weeks of training with the minimalist footwear. Afterwards, participants repeated the metabolic testing. Data was analyzed via repeated measures ANOVA. The analysis revealed a significant (F 4,32 = 7.576, ηp 2 =0.408, p≤0.001) interaction effect (time × treatment × speed). During the initial assessment, the minimalist footwear condition resulted in greater oxygen consumption at 9.6 km · hr -1 (p≤0.05) compared to the barefoot condition, while the running shoe condition resulted in greater oxygen consumption than both the barefoot and minimalist condition at 7.2 and 9.6 km · hr -1 . At post-testing the minimalist footwear was not different at any speed compared to the barefoot condition (p> 0.12). This study suggests that initially minimalist footwear results in greater oxygen consumption than running barefoot, however; with utilization the oxygen consumption becomes similar.